2006
DOI: 10.1109/jqe.2006.877222
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Compact Yb:YAG Ring Laser

Abstract: An efficient and compact Yb:YAG ring laser was demonstrated with a slope efficiency of 39.0% with respect to the absorbed power. The design issues for using Yb:YAG as the gain medium in the reentrant multipass ring laser are discussed. The high absorption coefficient and low quantum defect of Yb:YAG make it an ideal gain medium for the multipass ring cavity to fulfill reentrant condition and reduce reabsorption loss. The absorption characteristics of a 20-at.% doped Yb:YAG crystal and the optimum ratio of abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…such as Zeemax [6]). Reentrant rays in stable resonators afford some advantages for maintaining polarization states at laser outputs [7], or for reducing cavity lengths of some lasers [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…such as Zeemax [6]). Reentrant rays in stable resonators afford some advantages for maintaining polarization states at laser outputs [7], or for reducing cavity lengths of some lasers [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The MPRC [15][16][17] was constructed with a pair of identical spherical mirrors with the radius of curvature R, as shown in Fig. 1(a).…”
Section: Multipass Ring Cavitymentioning
confidence: 99%
“…Although the counter propagating beams in the cavity are expected to have the same round-trip optical path length, we observed that a small slight path length difference existed. 17) Using a fast photodiode to detect the beat frequencies of the longitudinal modes of the counter propagating beams, a 10.2 kHz difference in beat frequency was measured in the ð2; 1Þ MPRC. It is equivalent to an optical path length difference of 0.37 mm.…”
Section: (B)-5(d)mentioning
confidence: 99%
“…16,17) Besides microchip laser gain media, a thin Yb:YAG crystal is also eminently suitable for the multipass ring cavity (MPRC). 18) A thin crystal is less destructive to the beam path symmetry and helps to maintain the MPRC stability. With the proper package, the Yb:YAG crystal fiber is beneficial in improving the heat dissipation in the quasithree-level laser scheme.…”
Section: Introductionmentioning
confidence: 99%